Homologous cloning, characterization and expression of a new halophyte phytochelatin synthase gene in Suaeda salsa - 丛明 赵建民 吕家森 任志明 吴惠丰 (Chinese journal of oceanology and limnology, 2016)
The halophyte Suaeda salsa can grow in heavy metal-polluted areas along intertidal zones having high salinity. Since phytochelatins can effectively chelate heavy metals, it was hypothesized that S. salsa possessed a phytochelatin synthase （PCS） gene. In the present study, the cDNA of PCS was obtained from S. salsa （designated as SsPCS） using homologous cloning and the rapid amplification of cDNA ends （RACE）. A sequence analysis revealed that SsPCS consisted of 1 916 bp nucleotides, encoding a polypeptide of 492 amino acids with one phytochelatin domain and one phytochelatin C domain. A similarity analysis suggested that SsPCS shared up to a 58.6% identity with other PCS proteins and clustered with PCS proteins from eudicots. There was a new kind of metal ion sensor motif in its C-terminal domain. The SsPCS transcript was more highly expressed in elongated and fibered roots and stems （P〈0.05） than in leaves. Lead and mercury exposure significantly enhanced the mRNA expression of SsPCS （P〈0.05）. To the best of our knowledge, SsPCS is the second PCS gene cloned from a halophyte, and it might contain a different metal sensing capability than the first PCS from Thellungiella halophila. This study provided a new view of halophyte PCS genes in heavy metal tolerance.